Reasons and Expectations for Seeking Spiritual Treatment in Brazilian Spiritist Centers: A Qualitative Study - da Cunha, Carolina Roberta Ohara Barros e. Jorge (Journal of religion and health, 2024)
The objective of this study is to identify the main motivations and expectations for seeking spiritual treatment (ST) in spiritist centers. This is a qualitative study developed at two spiritist centers in the state of Mato Grosso, Brazil. ST was considered as the set of activities that use magnetic current as the main treatment method. We observed that most of the participants first sought treatments from health professionals and that, after insufficient results, they went in search of ST. Their treatments take place simultaneously and, for the participants, they complement each other. The motivations that led the participants to ST ranged from physical reasons to mental health complaints and even family conflicts. One possibility for investing in this type of treatment is due to the participants' desire for a more comprehensive approach, and not as a mere solution to the problem that directly afflicts them.